Geology and petrography of volcanic rock at Kampung Bukit Besi, Temangan, Kelantan - Nur Shafiqah Shahman (2017)
Igneous rock existing in Kelantan is volcanic rock and plutonic rock and volcanic rock consist in Kelantan are mostly distributed in area Tanah Merah, Machang and Rantau Panjang. The most abundant are pyroclastic deposits than lava flow. Tuff deposits are range from rhyolite to andesite composition that divided into crystal and lithic tuff pyroclastic rocks are predominantly than andesitic. The research area is Kampung Bukit Besi,Temangan where is district of Machang. Taku Shists Formation to the west and the east consists of shale and there have consists of quartz-porphyry dyke lie on contact to the east which there follow the regional strike and bedding, meanwhile east of the dyke the shale formation have interbedded with volcanic. The faults are indicated to present of the dyke, displacement of igneous rock. The objective for this research is to update the geological map of the research area. Besides that, this research is aim to identify characteristic and analyses petrography of volcanic rock in the research area. Petrography and X-ray diffraction techniques are used in this research study to determine the mineralogical composition of type volcanic rocks. Analyzation on the sample taken in the field are be done by thin section. Based on hand specimen the volcanic rock of the andesite the forming the name is the andesitic ignimbrite. However, based on petrography and the geochemistry analysis, the volcanic rock are found and are identify as naming of ignimbrite and andesite.